2008
DOI: 10.1002/chin.200805132
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Electrolytic Partial Fluorination of Organic Compounds. Part 89. Regioselective Anodic Fluorination of Tetrazolyl Sulfides.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Jończyk et al showed that 5-benzyl-1H-tetrazole reacted with chlorodifl uoromethane in the presence of concentrated aqueous sodium hydroxide and a catalyst, benzyltriethylammonium chloride (TEBAC), in THF with the formation of regioisomeric N-difl uoromethyl substituted derivatives 104, 105 [ 98 ]. An interesting approach to the synthesis of tetrazoles with fl uorine atoms in the side chain was suggested by Fuchigami et al who performed an anodic monofl uorination of 1-substituted 5-tetrazolyl sulfi des containing an α-electronwithdrawing group (EWG) leading to the formation of the corresponding C-F derivatives 105 [ 99 ]. …”
Section: Tetrazolesmentioning
confidence: 99%
“…Jończyk et al showed that 5-benzyl-1H-tetrazole reacted with chlorodifl uoromethane in the presence of concentrated aqueous sodium hydroxide and a catalyst, benzyltriethylammonium chloride (TEBAC), in THF with the formation of regioisomeric N-difl uoromethyl substituted derivatives 104, 105 [ 98 ]. An interesting approach to the synthesis of tetrazoles with fl uorine atoms in the side chain was suggested by Fuchigami et al who performed an anodic monofl uorination of 1-substituted 5-tetrazolyl sulfi des containing an α-electronwithdrawing group (EWG) leading to the formation of the corresponding C-F derivatives 105 [ 99 ]. …”
Section: Tetrazolesmentioning
confidence: 99%